USE OF SIMULTANEOUS OPERATIONS IN CHRONIC LEUKEMIAS - Ergashev Ulugbek Yusufjanovich; Mustafakulov Gaybulla Irisbaevich; Mominov Alisher Tashkarganovich; Gafurov Behzod Tohirovich; Minavarkhojayev Ravshankhuja Rakhmatkhuja ogli. (Scholar Express Journals, 2023)
This work presents observation data for 16 patients with hairy cell leukemia (HCL), the duration of the disease ranged from 1 to 15 years. The indications for surgery in case of ON and the results of splenectomy in 5 patients are presented. No complications from operations were observed. After splenectomy, the patients' condition improved platelets, blood retraction normalized, hemoglobin and erythrocytes rose in dynamics, hemorrhagic syndrome disappeared, hemodynamics stabilized. Despite the positive clinical and laboratory effect after splenectomy for a year, the further prognosis of the disease remains serious and patients need constant dispensary observation. Design and methods:We retrospectively analyzed the data on 127 patients (56 males, 71 females) with chronic immune thrombocytopenia between 2015 and 2019 in the Research Institute of Hematology of Republic of Uzbekistan. Results:The analysis of the results of the use of simultaneous surgeries in 17 (13.3%) of 127 patients with chronic immune thrombocytopenia was carried out. Taking into account the specifics of hematological pathology, the indications were determined for the most optimal options for such surgeries. Interpretation and conclusions:Simultaneous surgeries are a promising method for the treatment of several surgical diseases in hematological practice.
Keywords: blood diseases; splenectomy; simultaneous surgeries